2016 IEEE International Congress on Big Data (BigData Congress) 2016
DOI: 10.1109/bigdatacongress.2016.60
|View full text |Cite
|
Sign up to set email alerts
|

Towards Data Analytics of Pathogen-Host Protein-Protein Interaction: A Survey

Abstract: Abstract"Big Data" is immersed in many disciplines, including computer vision, economics, online resources, bioinformatics and so on. Increasing researches are conducted on data mining and machine learning for uncovering and predicting related domain knowledge. Protein-protein interaction is one of the main areas in bioinformatics as it is the basis of the biological functions. However, most pathogen-host protein-protein interactions, which would be able to reveal much more infectious mechanisms between pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Given a protein sequence denoted as X = denotes the amino acid types considered in the related projects). In our previous study [9], the protein sequence is decomposed into a 25*n dimension vector. In [18], the utilized database was from PISCES Cull PDB server and the ultimate datasets was filtered based on non-homologous principles.…”
Section: Machine Learning Methodologiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Given a protein sequence denoted as X = denotes the amino acid types considered in the related projects). In our previous study [9], the protein sequence is decomposed into a 25*n dimension vector. In [18], the utilized database was from PISCES Cull PDB server and the ultimate datasets was filtered based on non-homologous principles.…”
Section: Machine Learning Methodologiesmentioning
confidence: 99%
“…Their direct concatenate string becomes the sequence information of proteins. In [9], we give a detailed discussion of the 20 different proteinogenic kinds of amino acids and the sequence information of proteins. However, we have identified that there are 25 different expressions of amino acids existing in the human and pathogens protein sequence information in our PHPPI researches.…”
Section: A Structural Informationmentioning
confidence: 99%
See 3 more Smart Citations